Desain model pembelajaran e-learning berbasis moodle di Jurusan Pendidikan Teknik Elektronika - Sutarsi Suhaeb; Yasser Abd Djawad (Seminar Nasional LP2M UNM, 2019)
This study aims to find out how to design a Moodle-based e-learning learning model in the Electronics Engineering Education Department. E-learning is a learning model that uses a system or concept of education that utilizes information technology in the teaching and learning process. The software used in making e-learning is a Moodle course management system, Moodle is used to make a learning process that is carried out online and flexible. This research is a design research that carried out in the Electronics Engineering Education Department. The data analysis techniques that used is descriptive analysis. The results showed that the design of making E-learning learning models included indicators of visual elements, verbal elements, and design patterns obtained an average percentage score of 88.3% with very feasible and valid categories to be used. From the results of the study, it can be concluded that the design of making a moodle-based E-learning learning model that has been tested by media experts is very feasible, valid is used with the results of the calculation of the indicator score of 88.3%.